2009
DOI: 10.1016/s1081-1206(10)60190-1
|View full text |Cite
|
Sign up to set email alerts
|

Economic evaluation of sublingual immunotherapy vs symptomatic treatment in allergic asthma

Abstract: Background:The worldwide increased prevalence of allergic diseases, and especially of respiratory allergy, is paralleled by increased health costs. This requires consideration of the cost to efficacy ratio of the available treatment to identify the optimal choice.Objective: To compare the different economic relevance, over a long evaluation time, of symptomatic pharmacologic therapy and sublingual immunotherapy (SLIT) in patients with allergic asthma.Methods: Seventy patients with perennial allergic asthma, se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 24 publications
0
31
0
Order By: Relevance
“…Compared with patients receiving SDT alone, mean, annual per-patient costs (SLIT plus allergy-related medications) incurred by the patients receiving SLIT plus SDT were higher in year 1, equivalent in years 2 and 3, and significantly lower in years 4 and 5, with a net saving of 23%. The year 5 savings, in terms of annual per-patient incremental costs that were achieved by patients receiving SLIT plus SDT, increased with disease severity and reached 34% for severe asthmatic patients [228].…”
Section: Preventive Effects Of Aitmentioning
confidence: 98%
See 1 more Smart Citation
“…Compared with patients receiving SDT alone, mean, annual per-patient costs (SLIT plus allergy-related medications) incurred by the patients receiving SLIT plus SDT were higher in year 1, equivalent in years 2 and 3, and significantly lower in years 4 and 5, with a net saving of 23%. The year 5 savings, in terms of annual per-patient incremental costs that were achieved by patients receiving SLIT plus SDT, increased with disease severity and reached 34% for severe asthmatic patients [228].…”
Section: Preventive Effects Of Aitmentioning
confidence: 98%
“…The difference was even greater when future costs of asthma were included [226,227]. Ariano et al [228] conducted a costconsequence analysis alongside a prospective study of patients with allergic asthma due to HDM. Fifty patients received a 3-year course of SLIT plus SDT and 20 SDT alone.…”
Section: Preventive Effects Of Aitmentioning
confidence: 99%
“…Several individual studies and systematic reviews have been published, which suggests that immunotherapy is cost-effective as compared with standard symptomatic pharmacotherapy for AR and AR accompanied with asthma (ARAS) (61)(62)(63)(64)(65)(66)(67). These studies have consistently concluded that immunotherapy for 3 years was cost effective compared to pharmacotherapy with regard to symptom scores and quality of life improvements.…”
Section: Cost Effectiveness Of Immunotherapymentioning
confidence: 99%
“…These studies have consistently concluded that immunotherapy for 3 years was cost effective compared to pharmacotherapy with regard to symptom scores and quality of life improvements. Indeed, evidence indicates that immunotherapy is more cost-effective than standard symptomatic treatment when the social perspective and costs of productivity loss are taken into account (61)(62)(63)(64)(65)(66)(67). Furthermore, the cost effectiveness of immunotherapy is likely to be of greater magnitude when the long-term efficacy after termination of AIT treatment and the preventive effects of AIT on development of asthma and new sensitizations to allergens are considered (68)(69)(70)(71).…”
Section: Cost Effectiveness Of Immunotherapymentioning
confidence: 99%
“…An economic evaluation of SLIT was conducted by Ariano et al [11]. They compared the different economic aspects of symptomatic pharmacologic therapy and SLIT in patients with allergic asthma.…”
Section: Efficacy and Safetymentioning
confidence: 99%